Investigation into Class E/F3 with Parallel Network - Makarov, D.G.; Chernov, D.V.; Kryzhanovskyi, V.V.; Rassokhina, Yu.V.; Kryzhanovskyi, V.G.; Grebennikov, A.V. (Radiotekhnika, 2021)
The system of equations for processes in the amplifier output network is analytically formulated. This system of equations considers parameters of resonant networks at higher harmonics. To calculate amplifier output network, the system of five equations was built for five unknowns, to which the condition of positive second voltage derivative at extremum of drain voltage was added. Two equations correspond to class E conditions, another two — quadrature waveforms at load and at additional resonant network. The last equation is the condition of extremum at the point near middle of drain voltage pulse. This system was solved using computer algebra program. The circuit elements and waveforms were calculated using the derived parameters. By choosing different parameters, it is possible to obtain various amplifier realizations, which will demonstrate features of different class F variants. The obtained amplifier parameters drain voltage and current waveforms were verified with calculated ones using the harmonic balance simulating software. The variant, which is closer to class E/F3 mode, was chosen to build an experimental amplifier prototype on frequency 2MHz using IRF530 MOSFET as a switch. The prototype was tested in the range of supply dc voltage up to 24V with the output power greater than 6W, while the amplifier efficiency was >80%. In the experiment, the ratio of peak drain voltage to dc supply voltage was measured to be 3.3 at the duty ratio 50%, unlike class E amplifier, where this value is around 3.65, and on practice, considering non-linear drain to source capacitance, it may achieve 4. The experimental second harmonic level amounted to be -20 dB relatively to fundamental, and the third one — 28.5 dB, which is due to an additional second harmonic filter. The paper results are useful for introduction of such circuits to practice.